Feeding larvae meal in broiler diets and its effect on growth performance - Alshelmani, Mohamed Idris; Loh, Teck Chwen; Kareem, Karwan Yaseen; Abdulla, Nazim Rasul; Foo, Hooi Ling; Mohd Zamri, Amirah Nabilah; Shazali, Nurhazirah (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
Larvae meal has been reported as a suitable alternative protein source to fish meal and soybean meal. It contained necessary essential amino acids required in poultry feeding. An experiment was conducted to assess the effects of different levels of larvae meal on broiler performance. A total of 216 one-day-old male broiler chicks were raised for 42 days. Birds were randomly allotted into open house cages and 6 chicks per cage. The dietary treatments were supplemented with larvae meal by 0%, 2%, 4%, 6%, 8% and 10% to represent T1, T2, T3, T4, T5 and T6, respectively. The findings showed that body weight, average daily gain and total weight gain for T1 were significantly decreased (P<0.05) compared to T5 and T6.